The Effectiveness of Extracurricular Educational Programs in Educating Adolescents through National Values (Journal of Educational Sciences, 2025)
The formation and development of national values among adolescents in the context of globalization and the information society is very important. This article is devoted to the study of the effectiveness of extracurricular educational programs in the education of national values among adolescents. The main purpose of the work is to assess the impact of various extracurricular programs on the formation of a sense of national identity, patriotism and respect for cultural heritage among adolescents. The article provides a theoretical justification of the importance of national values in the development of the personality of adolescents. The plan of the program of the circles is described on the basis of entertainment, scientific and educational, sports and recreation, value-oriented, artistic, aesthetic and technical creative, labor and professional activities, military-patriotic activities, tourist and local history activities aimed at fostering national values. For the empirical study, methods of interviewing and solving situational questions were used for adolescents participating in various extracurricular programs, as well as their parents. The results showed that the created extracurricular educational programs aimed at studying and preserving the national cultural heritage have a significant impact on the formation of a positive attitude towards their country and a sense of pride in the country among adolescents. The results of the study confirm the need and importance of introducing extracurricular programs into the education system of adolescents to strengthen national values. The article contains recommendations for teachers and developers of educational programs on optimizing the content and methods of extracurricular work in order to increase the effectiveness of education of national values.Key words: extracurricular education, national values, adolescence, patriotism.